Pengaruh Media Konkret Terhadap Hasil Belajar Matematika Siswa Kelas 2 SD Negeri Bojong 3 Kota Tangerang - Fitriana, Ratih; Amaliyah, Aam; Unaenah, Een (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine whether or not there is an influence of Concrete media on Student Learning Outcomes in Mathematics. The method used in this study is Quasi Experimental and Conventional. The hypothesis put forward in this study is: "There is an influence of teaching concrete media on the mathematics learning outcomes of grade 2 students at SDN Bojong 3 Kota". This research was conducted at SDN Bojong 3 Pinang Tangerang grade 2 in the odd semester of the 2022-2023 school year. The sample studied was 60 students consisting of 30 students from the experimental class and 30 students from the control class. The study showed that the results of the final test of the experimental class and the control class with the Paired Sample Test T-test obtained a (2-tailed) value of 0.000 and sig. 0.05 the results of this study concluded that there was an influence on student learning outcomes by using the concrete of Teaching with students who were taught by conventional models.